Prolonged neuroglycopenia in a type 1 diabetic pregnancy: a case report - Nhalil, Kusumam Vilangot; Mathew, Marin Mariyam; Narayanan, Saikrishna; Balathil, Ranjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Hypoglycemia in pregnancy is a metabolic abnormality associated with substantial morbidity. Here we report the adverse events triggered during pregnancy in a primi with type 1 diabetes. A 19-year-old primi, type 1 diabetic since 13 years of age and history of recurrent seizures since fourth month of pregnancy presented at 28 weeks with severe hypoglycemia. Clinico-radiological impression of a metabolic encephalopathy secondary to prolonged neuroglycopenia was kept. She underwent preterm caesarean section and delivered a 1.86 kg baby. She was weaned off the ventilatory support and discharged on POD 38 on tracheostomy T piece. After that she continued treatment from local hospital, and expired 2 weeks later. presently her child is 4 years old, healthy with age-appropriate milestones.